Recovery of glucose from residual starch of sago hampas for bioethanol production - Awang Adeni, Dayang Salwani; Bujang, Kopli; Hassan, Mohd Ali; Abd. Aziz, Suraini (Hindawi Publishing Corporation, 2013)
Lower concentration of glucose was often obtained from enzymatic hydrolysis process of agricultural residue due to complexity of the biomass structure and properties. High substrate load feed into the hydrolysis system might solve this problem but has several other drawbacks such as low rate of reaction. In the present study, we have attempted to enhance glucose recovery from agricultural waste, namely, “sago hampas,” through three cycles of enzymatic hydrolysis process. The substrate load at 7% (w/v) was seen to be suitable for the hydrolysis process with respect to the gelatinization reaction as well as sufficient mixture of the suspension for saccharification process. However, this study was focused on hydrolyzing starch of sago hampas, and thus to enhance concentration of glucose from 7% substrate load would be impossible. Thus, an alternative method termed as cycles I, II, and III which involved reusing the hydrolysate for subsequent enzymatic hydrolysis process was introduced. Greater improvement of glucose concentration (138.45 g/L) and better conversion yield (52.72%) were achieved with the completion of three cycles of hydrolysis. In comparison, cycle I and cycle II had glucose concentration of 27.79 g/L and 73.00 g/L, respectively. The glucose obtained was subsequently tested as substrate for bioethanol production using commercial baker’s yeast. The fermentation process produced 40.30 g/L of ethanol after 16 h, which was equivalent to 93.29% of theoretical yield based on total glucose existing in fermentation media.